Study of Cows’ Behaviour and Welfare on Dairy Farms in Serbia - Dušica Ostojić Andrić (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2019)
Modern methods for assessing the welfare of dairy cows are, among other things, often based on the evaluation of animal behaviour. In this regard, behaviour is classified as the most reliable, so‑called animal‑based indicator as its expression comes from the animal itself and indicates a measure in which it has adapted to the environment. Starting from the need to explore the state of welfare and the ability to demonstrate adequate behaviour in dairy farms in Serbia, the Welfare Quality® Assessment Protocol for Cattle (2009) was used in this study. The overall assessment of behaviour was carried out by analysing four main criteria: social, other forms of behaviour, human‑animal relationship and emotional state. The results of the study conducted on a total of 16 dairy farms (N = 4,833 cows) show that the conditions for ensuring appropriate behaviour meet only minimum standards and that the greatest welfare risks arise from the impossibility of expressing natural behaviour, such as exploratory behaviour. The most pronounced negative tendencies within the assessment of the emotional status were those expressed to distress, frustration and boredom. Although the estimated general condition does not differ substantially from the same on EU farms, the need for its improvement is imposed first of all in terms of ensuring greater freedom of movement and more stimulating environment in cattle rearing.